Redistribution with growth : policies to improve income distribution in developing countries in the context of economic growth : a joint study [commissioned] by the World Bank's Development Research Center and the Institute of Development Studies, University of Sussex - World Bank; Chenery, Hollis Burnley; World Bank.; Institute of Development Studies (Brighton, England) (London : Published for the World Bank and the Institute of Development Studies, University of Sussex [by] Oxford University Press, 1974)
Synthesis of papers discussed at a workshop convened at the Rockefeller Foundation Conference Center in Bellagio, April, 1973, and at the Conference on Redistribution with Growth at the Institute of Development Studies, Sept., 1973.
Bibliography: p. [291]-304.
usc 06/07/2017
Loans
Keywords: Income distribution; Income distribution; Developing countries